2017
DOI: 10.1098/rsos.170349
|View full text |Cite
|
Sign up to set email alerts
|

Do pet dogs ( Canis familiaris ) follow ostensive and non-ostensive human gaze to distant space and to objects?

Abstract: Dogs are renowned for being skilful at using human-given communicative cues such as pointing. Results are contradictory, however, when it comes to dogs' following human gaze, probably due to methodological discrepancies. Here we investigated whether dogs follow human gaze to one of two food locations better than into distant space even after comparable pre-training. In Experiments 1 and 2, the gazing direction of dogs was recorded in a gaze-following into distant space and in an object-choice task where no cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 55 publications
3
48
3
Order By: Relevance
“…This latter hypothesis is also consistent with the gazing behaviour observed in the present study: dogs gazed where their owner gazed. This is congruent with recent studies on gaze following into distant space that emphazises the effect of training as well as daily experiences in gaze following behaviour 37 , 38 . This suggests that social cognition, learning and affiliation are involved in the synchronization of dogs’ behavior with that of the owner, confirming that the optomotor reflex hypothesis is less likely.…”
Section: Discussionsupporting
confidence: 91%
“…This latter hypothesis is also consistent with the gazing behaviour observed in the present study: dogs gazed where their owner gazed. This is congruent with recent studies on gaze following into distant space that emphazises the effect of training as well as daily experiences in gaze following behaviour 37 , 38 . This suggests that social cognition, learning and affiliation are involved in the synchronization of dogs’ behavior with that of the owner, confirming that the optomotor reflex hypothesis is less likely.…”
Section: Discussionsupporting
confidence: 91%
“…While it has been shown that infants develop an expectation that the direction of ostensive gaze is referential and it delivers generalizable knowledge (Senju et al, 2008 ), much less research addressed how humans interpret non-ostensive gaze. In contrast to the infants' performance, a number of studies found that without training and extended experimental pre-experiences, dogs follow communicative human gaze only with their gaze but do not approach a food location indicated in this way (Kaminski et al, 2012 ; Téglás et al, 2012 ; Duranton et al, 2017 ). Furthermore, dogs do not only ignore non-ostensive gaze but in fact tend to avoid a food location that another dog or a human has looked at in this way beforehand (Bálint et al, 2015 ; Duranton et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dogs have also been believed to use human gaze similarly to pointing, often ignoring findings that even after a communicative gaze cue, dogs choose one of two food locations randomly (Kaminski et al, 2012 ). Differences in the two species' reactions to directional cues have been further highlighted by recent studies showing that while children ignore gaze cues in a non-ostensive context (Senju and Csibra, 2008 ), dogs actually avoid food locations indicated with non-communicative gaze by both a conspecific and a human (Bálint et al, 2015 ; Duranton et al, 2017 ). Based on these findings, it has been hypothesized that dogs see an object choice task with non-communicative gaze as food competition and they tend to behave in a way that can help to avoid a potential conflict over food (Duranton et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more research is needed to fully establish the impact of this close evolutionary history, it is clear that dogs have developed strikingly human-like interpretations of human communicative cues across domestication. Not only do dogs follow human communicative cues from an early age (Hare et al, 2002;Riedel et al, 2008;Rossano et al, 2014), but they also seem to expect this information will be referential in the same way as human children (Duranton, Range, & Virányi, 2017;Miklósi et al, 1998;Soproni, Miklósi, Topál, & Csányi, 2001;Téglás et al, 2012). Given dogs' close evolutionary history with humans and their human-like sensitivity to communicative cues, they provide an ideal comparison species for pinpointing which particular aspects of human sensitivity to communicative cues uniquely support human culture.…”
mentioning
confidence: 99%